Smart City and Modelling of Its Unorganized Flows Using Cell Machines - Truong Thanh Trung (Civil Engineering Journal, 2020)
The evolution of the digital economy requires the appropriate infrastructure for administrative management and support of “Smart City". All this makes it possible to look at the problems of the city in a new way. SMART-city is an integrated infrastructure, an environment for improving the comfortable life and work of all citizens. In urban traffic flows, there are obstacles in place where traffic flow is not organized. In these places, special solutions, management measures and safety criteria are required. Such flows and situations should be simulated. This problem is solved based on flow-intensive management criteria using situational scenarios. The efficiency of flow management on busy highways requires the consideration of critical factors. In the present work, such a task is investigated using cell machines, which showed efficiency in streaming tasks of gas dynamics. A purpose of work and its result is a decline system's complexity and dimension by means of linearization and reduction of algorithmic complexity. The field of cells is considered. If there’s an obstacle in the cell then the direction by which the obstacle affects minimally is selected (Stochastic assessment has been used). System analysis of SMART-city problems is also carried out in this work. Adaptive IT infrastructure, security, virtualization, risk and the multi-criteria decision-making in an uncertain environment has been analyzed.